The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/membranes11050343
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Amino Acid-Based Permeation Enhancers in Transdermal Drug Delivery

Abstract: Transdermal drug delivery (TDD) presents many advantages compared to other conventional routes of drug administration, yet its full potential has not been achieved. The administration of drugs through the skin is hampered by the natural barrier properties of the skin, which results in poor permeation of most drugs. Several methods have been developed to overcome this limitation. One of the approaches to increase drug permeation and thus to enable TDD for a wider range of drugs consists in the use of chemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 114 publications
(167 reference statements)
0
19
0
3
Order By: Relevance
“…In a similar spirit, the use of conjugated antioxidants with antiretroviral drugs has been proposed to increase drug penetration into the central nervous system [599]. Additionally, peptides, including antimicrobial peptides, were proposed as an effective enhancer [600,601]. Recent MD simulations demonstrated that glycyrrhizic acid enhanced the translocation of the antiparasitic drug praziquantel through a lipid bilayer by lowering the free energy barrier associated with the hydrophobic center of the membrane along with a rearrangement of the lipid headgroups [252].…”
Section: Translocation Through the Membranementioning
confidence: 99%
“…In a similar spirit, the use of conjugated antioxidants with antiretroviral drugs has been proposed to increase drug penetration into the central nervous system [599]. Additionally, peptides, including antimicrobial peptides, were proposed as an effective enhancer [600,601]. Recent MD simulations demonstrated that glycyrrhizic acid enhanced the translocation of the antiparasitic drug praziquantel through a lipid bilayer by lowering the free energy barrier associated with the hydrophobic center of the membrane along with a rearrangement of the lipid headgroups [252].…”
Section: Translocation Through the Membranementioning
confidence: 99%
“…While physical and nanotechnological approaches like those addressed in previous sections undeniably lie at the forefront of dermal and transdermal drug delivery research, CPEs remain the simplest and most cost-effective way to permeate different solutes across the skin, and their use is widely disseminated [ 116 ]. This explains the strong interest towards a better understanding of their modes of action [ 10 , 117 ] and on development of novel CPEs, searching for greener and more biocompatible alternatives, such as those derived from essential oils [ 118 ] or amino acids [ 4 ].…”
Section: Overview Of Current Methods For Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“… Schematic view of skin permeation pathways: intercellular, transcellular, and transappendageal [ 4 ]. Reprinted with permission from ref.…”
Section: Figurementioning
confidence: 99%
“…Another approach to lower enhancer toxicity exploits natural compounds 5,7 . Natural compounds have successfully been used as the polar heads of amphiphilic enhancers (such as α-and ω-amino acids [8][9][10][11][12][13][14][15][16] and sugars) or their lipophilic tails (e.g., terpene moieties) 17 .…”
Section: Abbreviationsmentioning
confidence: 99%